Audit Keamanan Sistem Informasi IT Di PT X - Fandy Arya Gunadi; Adi Wibowo; Ibnu Gunawan (Jurnal Infra, 2015)
Established on July 10, 1991 in Sidoarjo, East Java, PT X is a company engaged in the field of general printing, especially printing commercial documents. In carrying out its business processes, the company is using software, hardware, network, and machines used for the production process. But the company was less concerned about security for asset and data owned companies. Though the data and information are now becoming a very important asset. Thus the required audit information system that aims to analyze the extent to which extent the company's information system security.This thesis analyzed informationsystem security audit of IT in PT. X. The steps in the audit analysis is by using COBIT 4.1 standards. Problems were found in the company of, among others, there is no assignment letter given to employees of IT in PT X, no monthly report on IT security made by the IT division of PT X, there is no IT security standards as the reference in the company, not using cryptographic key features implemented in protecting data and information.The response given to the company that the company should make a task and make monthly reports on IT security. Soon also to make IT security standards and create cryptographic keys for protecting and and information held by company.In this study discusses one domain that Deliver and Support of 4 domain in COBIT the discussion is limited to Ensure systems security (DS5).